Some Aspects of Surface Integrity after Hard Milling - Neslusan, Miroslav; Cillikova, Maria; Uricek, Juraj; Micietova, Anna; Capek, Jiri (Manufacturing Technology Journal, 2018)
This paper deals with surface integrity after hard milling of bearing steel 100Cr6. Surface integrity is expressed in terms of shape deviation as well as Barkhausen noise emission. Furthermore, components of cutting forces are also measured as a function of tool wear. Non homogeneity of cutting force distribution within the contact between the milling cutter and workpiece is discussed. The results of measurements indicate that shape as well as structure remarkable non homogeneity should be expected after hard milling due to missing full contact between milling cutter and workpiece. This non homogeneity can be monitored via Barkhausen noise technique. On the other hand, the competitive grinding cycles produced more homogenous surface and surface state is a function of infeed speed.
Keywords: hard milling; grinding; surface integrity; Barkhausen Noise